Strategies For Empowering Micro, Small, And Medium Enterprises (Msmes) Through Halal Certification Education And Assistance To Improve Product Quality And Consumer Trust: A Case Study On Msmes In The Special Region Of Yogyakarta - Hanif Kistoro; Elfi yuliani Rochmah; Rubini (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
The empowerment of Micro, Small, and Medium Enterprises (MSMEs) faces significant challenges in the era of global competition, especially related to product standardization and halal assurance. This study examines the strategy of empowering MSMEs through halal certification education and assistance programs as an effort to improve product quality and consumer trust. The research aims to identify the factors that affect the effectiveness of halal certification programs and their impact on the development of MSMEs. A qualitative approach with a case study design was used in this study, involving 15 MSME actors participating in the halal certification program in Ambarketawang Village, Gamping District, Sleman Regency, Special Region of Yogyakarta. Data were collected through in-depth interviews, participatory observation, and document analysis, then analyzed using thematic analysis techniques. The findings of the study reveal four main themes: the transformation of halal literacy and product assurance system awareness, the reconstruction of production practices towards halal standardization, increasing consumer confidence and expanding market access, and strengthening the institutional capacity of MSMEs. The results of the study show that intensive mentoring and continuous education contribute significantly to the successful implementation of halal certification. This research contributes to the understanding of MSME empowerment practices based on halal certification and provides strategic recommendations for stakeholders in the development of a sustainable MSME ecosystem.